Drying shrinkage of gunny fabric fiber (GFF) concrete - Md Noor, Nurazuwa (2010)
Gunny sack is made fiom natural fiber which is$kxible, has high tensile strength, low extensive and environmentally friendly. All these advantages gave potential to gunny to be utilized in concrete as fiber. n i s paper discussed the potential of gum? faabriccfiber (GFF) with size 1 cm and 4 crn as an &rive fiber in concrete to improw +mg shrinkage behavior. D@ng shrinkage is the concrete long term behavior which could lead to cruckproblem. ?hree series of beam with size 500 mm x 100 mm x 100 mm were mix rad butch accordrng to Deparfmernt of Environmental @WE) and tested for 3, 7, 14, 28, 56 and 72 days. Ihe series incZ&s control mix? 1 cm GFF with addition of 1 %, 3% and 5% and 4 cm GFF with addition of 1% 3% md 5% in concrete. Fly ash was added 10% to all series of concrete mix as cement replacement. It showed the addition of 1 % of 1 cm GFF gave the lowest drying shrinkage value compared with all other series. n i s series of mix has the potential as discrete fiber reinforcement to reduce the concrete shrihge hence minimize the concrete crack.